Convergence in Maximum Stomatal Conductance of C3 Woody Angiosperms in Natural Ecosystems Across Bioclimatic Zones - Murray, Michelle; Soh, Wuu Kuang; Yiotis, Charilaos; Batke, Sven; Parnell, Andrew C.; Spicer, Robert A.; Lawson, Tracy; Caballero, Rodrigo; Wright, Ian J.; Purcell, Conor; McElwain, Jennifer C. (Frontiers in Plant Science, 2019)
Stomatal conductance (gs) in terrestrial vegetation regulates the uptake of atmospheric carbon dioxide for photosynthesis and water loss through transpiration, closely linking the biosphere and atmosphere and influencing climate. Yet, the range and pattern of gs in plants from natural ecosystems across broad geographic, climatic, and taxonomic ranges remains poorly quantified. Furthermore, attempts to characterize gs on such scales have predominantly relied upon meta-analyses compiling data from many different studies. This approach may be inherently problematic as it combines data collected using unstandardized protocols, over decadal time spans and from different habitat groups. Using a standardized protocol we measured leaf-level gs using porometry in 218 C3 woody angiosperm species in natural ecosystems representing seven bioclimatic zones. The resulting dataset of 4273 gs measurements, which we call STraits (Stomatal Traits), was used to determine patterns in maximum gs (gsmax) across bioclimatic zones and in particular whether there was convergence in gsmax across ecosystem types. We also tested for differential gsmax in two broadly-defined habitat groups - open-canopy and understory-subcanopy - within and across bioclimatic zones. We found strong convergence in mean gsmax in the understory-subcanopy habitats across six bioclimatic zones, but not in open-canopy habitats. Mean gsmax in open-canopy habitats (266 ± 100 mmol m-2 s-1) was significantly higher than in understory-subcanopy habitats (233 ± 86 mmol m-2 s-1). There was also a central tendency in the overall dataset to operate towards a gsmax of ~250 mmol m-2 s-1. We suggest that the convergence in the understory-subcanopy is due to a buffering of gsmax against macroclimate effects which will lead to differential response of woody vegetation in these two habitats to future global change. Therefore, it will be important for future studies of gsmax to categorize vegetation according to habitat group.